An efficient palladium oxide nanoparticles@Co3O4 nanocomposite with low chemisorbed species for enhanced oxygen evolution reaction. (19th January 2022) - Solangi, Muhammad Yameen; Aftab, Umair; Tahira, Aneela; Abro, Muhammad Ishaq; Mazarro, Raffaello; Morandi, Vitorio; Nafady, Ayman; Medany, Shymaa S.; Infantes-Molina, Antonia; Ibupoto, Zafar Hussain
Abstract: Significant progress has been made in recent time to design and synthesize highly efficient and cost effective electrocatalysts for oxygen evolution reaction (OER). However, the electrocatalytic activity of most recently reported materials is limited by the large onset potential, poor electrical conductivity and low density of catalytic centers. In this study, we report facile deposition of palladium oxide nanoparticles onto cobalt oxide nanostructures (PdONPs@Co3 O4 ) through the illumination of ultraviolet (UV) light. The fabricated PdONPs@Co3 O4 nanocomposites offer high density of active sites, improved electrical conductivity and durability for OER activity. The synergetic effect between the Co and Pd ions at the interface of composite system might change the adsorption energy of reaction intermediates, thus enabled the reaction to proceed at lower energy consumption. Significantly, the prepared PdONPs@Co3 O4 samples demonstrated a low overpotential of 250 mV at a current density of 20 mA/cm 2, with low charge transfer resistant of 48.5 Ωand high durability for more than 40 h during OER processes. The combined results suggest that incorporating of a low amount of PdONPs can tune the surface properties of Co3 O4 and interfacial chemistry. This could led to accelerate the charge transport properties at the interface during a specific electrochemical application. Graphical abstract: The graphical abstract shows the synthesis of Co3 O4 nanostructures, and their composite with the palladium oxide nanoparticles, chemical composition, morphology and electrocatlytic activities towards oxygen evolution reaction in alkaline media. Image 1 Highlights: Low chemisorbed species on the Pd@Co3 O4 nanocomposite are observed. A low OER overpotential of 250 mV was found at 20 mAcm −2 . The Pd@Co3 O4 nanocomposite exhibited a durability of 40 h.